Comparison of IL-6 Levels After Ibuprofen–Paracetamol– Dexamethasone in Percutaneous Nephrolithotomy Patients: an Analytic Observational Study - Rozi, Fakhriyadi (Udayana University and Indonesian Society of Anesthesiologists (PERDATIN), 2025)
Introduction: Percutaneous Nephrolithotomy (PCNL) is the therapeutic procedure of choice for kidney stones. IL-6 secretion is stimulated during a secondary inflammatory response due to tissue injury or infection. Proper administration of analgesics can reduce morbidity rates, reduce treatment days, and reduce financing. Patients and Methods: An analytical observational study with a cross-sectional design at Purwokerto tertiary hospital in the period from December 2024 to January 2025 in patients undergoing PCNL procedures and receiving ibuprofen, paracetamol, and dexamethasone therapy, which met the inclusion and exclusion criteria. The observational group (15 patients each) was: Group A 1000 mg paracetamol and 400 mg ibuprofen and 5 mg dexamethasone; Group B 1000 mg paracetamol and 400 mg ibuprofen. IL-6 levels were measured before and 2 hours after the PCNL procedure. IL-6 levels were measured by ELISA (enzyme-linked immunosorbent assay). Comparative analysis of pre- or post-PCNL IL-6 levels by type of analgesic using unpaired t-test, while the comparison of changes in IL-6 levels was analyzed with the Mann-Whitney test. To determine whether the data distribution was normal, we used the Shapiro-Wilk test. The analysis used SPSS version 25. Results: Pre- and post-PCNL IL-6 levels were significantly lower in Group A compared to Group B (p < 0.05). However, changes in IL-6 levels were not statistically significant (p = 0.787). Effect size analysis indicated only a small and clinically negligible difference. Conclusion: There was no significant difference in IL-6 levels post-PCNL between the two observation groups.